Improving Students’ Vocabulary Mastery in Descriptive Text through Picture and Word Matching Technique at the Seventh Grade of SMP Negeri 3 Pematangsiantar - Pardede, Dwi Angeli; Selviana Napitupulu (CV PUTRA PUBLISHER, 2025)
This classroom action research investigated the effectiveness of the Picture and Word Matching Technique in enhancing the vocabulary mastery of seventh-grade students at SMP Negeri 3 Pematangsiantar. The study involved 30 students of Class VII-5 and was conducted in two cycles following the stages of planning aniani4d, action, observation, and reflection. Data were obtained through vocabulary tests, classroom observations, and field notes. The results showed a consistent increase in students' vocabulary performance. The mean score improved from 60.00 in the pre-test to 73.33 in Cycle I and reached 86.00 in Cycle II. The percentage of students achieving the minimum mastery criterion (75) rose from 20% to 90%. Qualitative findings indicated higher student participation, stronger motivation, and more accurate vocabulary use during learning activities. The combination of visual support and word recognition tasks helped students recall and apply new vocabulary more effectively. Overall, the Picture and Word Matching Technique proved to be an effective approach for improving students' vocabulary mastery in descriptive text learning.